Síntese a partir de baterias exauridas de íon-Li e Zn-MnO2 de Fe3O4, CoFe2O4 e ZnFe2O4 e suas aplicações como catalisadores nas reações de foto Fenton heterogêneo - Moura, Mayra Nicoli (2017)
Cathode cobalt of the lithium-ion battery (LIBs) depleted of Samsumg®cell phones was recycled as cobaltdoped ferrite. Anode zinc of alkaline batteries (Zn-MnO2) Duracell®AA was recycled for the formation of zincdoped ferrite. The ferrites were applied as catalysts in heterogeneous photo Fenton reactions for the discoloration of the blue dye of methylene. The X-ray diffraction (XRD) analysis revealed the formation of ferrites spinel no doped, cobalt doped and zinc doped. With the aid of the techniques: scanning electron microscopy (SEM) and transmission electron microscopy (TEM), it was verified that the no doped, cobalt doped and zinc doped ferrites form agglomerates of nanometric particles. By the analysis of Inductively Coupled Plasma Optical Emission Spectrometry (ICP OES) and Flame Atomic Absorption Spectroscopy (FAAS) it was possible to determine the concentrations of the metals present in the ferrites. The cobalt concentrations were 70.0 ± 4.0 mg.g-1and 65.0 ± 2.0mg.g-1in cobalt doped ferrites from analytical reagent and lithium-ion battery, respectively. The zinc concentrations in the zinc doped ferrites from the analytical reagent and the alkaline battery were respectively 26.0 ± 1.0mg.g-1and 89.0 ± 4.0mg.g-1. The optimized condition for the discoloration of the dye was evaluated by a factorial planning. The best condition for the catalytic reaction using CoFe2O4as catalyst was pH 3.0, 30 mg of catalyst and 8 mL of H2O2, obtaining the percentage of degradation efficiency equal to 61.5%, 87.3% and 87.7% for no doped ferrite, cobalt doped from analytical reagents and cobalt doped from Li-ion and CoFe2O4-LIBs leached solution, respectively, after 420 minutes. The doping improved the discoloration efficiency of the methylene blue solution. The best optimized experimental condition for ZnFe2O4was pH 6.0, 30 mg of catalyst and 8 mL of H2O2, with discoloration efficiency in the study of 45.9%, 92.2% and37.0% for no doped ferrite, zincdoped from analytical reagent and zinc doped from leached alkaline battery, after 240 minutes of reaction